Precursor for forming lanthanide-containing metal thin film, method for forming lanthanide-containing metal thin film using said precursor, and semiconductor element comprising said lanthanide-containing metal thin film

By introducing cyclopentadienyl and amidinyl ligands into the precursor for film formation, the physical properties of the precursor are optimized, and the problems of high viscosity and low volatility in film formation in the prior art are solved, and high quality is achieved Film formation and improvement of dielectric properties.

CN119403955APending Publication Date: 2025-02-07SK TRICHEM
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380048812.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-15
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When forming a high dielectric film, the leakage current is prone to deterioration due to the band gap, and the commonly used precursor materials have high viscosity and low volatility, making it difficult to meet the needs of film formation.

Method used

A precursor for forming a lanthanum-containing metal film was developed. Through the chemical structure containing cyclopentadienyl and amidinyl ligands, the low viscosity, high volatility and heat resistance of the precursor were optimized to form high quality. film.

Benefits of technology

The film formation with low viscosity, high heat resistance and high volatility is achieved, and the dielectric constant and leakage current characteristics of the film are improved, which is suitable for the manufacturing of high dielectric films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403955A_ABST
    Figure CN119403955A_ABST
Patent Text Reader

Abstract

The present invention relates to a precursor for forming a lanthanum-group-containing metal thin film comprising a compound represented by chemical formula 1, the precursor comprising a lanthanum-group metal as a central metal atom, a method for forming a lanthanum-group-containing metal thin film using the precursor, and a semiconductor element comprising the lanthanum-group-containing metal thin film. The cyclopentadienyl ligand is used for realizing the characteristics of low melting point, high volatility and the like, and the novel amidinyl ligand is used for realizing the characteristics of relatively high structural stability, low viscosity, high volatility, high heat resistance, normal-temperature liquid state or solid state with relatively low melting point and the like. As a result, it is possible to exhibit physical properties suitable for use in a film formation process and thereby form a high-quality film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a precursor for forming a lanthanum group metal film, a method for forming a lanthanum group metal film using the precursor, and a semiconductor component containing the lanthanum group metal film, and more particularly to a precursor for forming a lanthanum group metal film that can form a low viscosity, high heat resistance, and high volatility precursor through a chemical structure containing an amidine ligand, thereby forming a high-quality film, a method for forming a film using the precursor, and a semiconductor component containing the film. Background Art

[0002] As the integration level of semiconductor components is improved due to the miniaturization of the line width, the space allowed for realizing the capacitor structure is limited by the line width. Therefore, the manufacturing method of semiconductor components for realizing the capacitor structure is also limited in the existing organic silicon dielectrics. In particular, when high dielectric films are used to replace organic silicon dielectrics, the leakage current will be greatly degraded due to the band gap.

[0003] As one of the solutions to the above-mentioned problems, a technology capable of forming a high-quality thin film is required, and for this purpose, it is necessary to optimize the precursor used when forming the thin film.

[0004] As an example of existing precursor optimization solutions, a variety of doping precursors that can improve dielectric constants and leakage current characteristics have been proposed, but the corresponding precursors are generally solid phases or low-volatility liquid phases, and may induce various problems in the thin film deposition process due to their high viscosity. Therefore, in order to optimize the thin film forming precursor, improving the physical properties of the precursor, such as high volatility and low viscosity, is a very important issue.

[0005] To this end, a variety of metal-containing precursors have been developed. For example, Korean Patent Publication No. 10-2019-0008427 discloses a lanthanum metal precursor containing an azallyl ligand, and Korean Patent Publication No. 10-2019-0094238 discloses a lanthanum metal precursor containing a cyclopentadienyl ligand.

[0006] In particular, the cyclopentadienyl-containing complex has a lower melting point and higher volatility than the β-diketone- or bis(trimethylsilyl)amide-containing compounds, and is therefore more advantageously used as a precursor in the thin film forming process.

[0007] For the reasons mentioned above, in the known technologies such as Korean registered patent No. 10-1660052, Korean patent No. 10-2019-0109142 and No. 10-2021-0084297, a chemical structure combining a cyclopentadienyl group and an amidine group as a ligand as a lanthanum group metal precursor is proposed. The report points out that the precursor combined with the ligand as described above can improve the disadvantages of the existing lanthanum group metal precursor with low vapor pressure and high viscosity, and is suitable for use in thin film formation engineering. Summary of the invention

[0008] An object of the present invention is to solve the above-mentioned problems existing in the prior art and to provide a novel lanthanum group metal-containing thin film forming precursor which can exhibit chemical properties suitable for a thin film forming precursor.

[0009] Another object of the present invention is to provide a lanthanum group metal thin film forming precursor which exhibits chemical characteristics of low viscosity, high heat resistance and high volatility and is in a liquid state or a solid state with a relatively low melting point at room temperature.

[0010] Another object of the present invention is to provide a method for forming a thin film using the precursor.

[0011] Another object of the present invention is to provide a semiconductor component comprising the thin film.

[0012] In order to achieve the above-mentioned object, the precursor for forming a lanthanum group metal thin film of the present invention is characterized by comprising a compound represented by the following Chemical Formula 1.

[0013]

Chemical formula 1

[0014]

[0015] In the chemical formula, M is a lanthanide metal, R1 and R2 are each independently a C1-C5 straight chain, branched or cyclic alkyl or alkenyl group, R2 is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, R' is the same as or different from each other and is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, and n is an integer from 1 to 5.

[0016] In addition, the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.

[0017] In addition, the R1 and R3 may each independently be a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.

[0018] In addition, the R1 and R3 may be methyl groups.

[0019] In addition, the R2 may be an isopropyl group.

[0020] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group.

[0021] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group, and the R2 may be a C1-C4 straight-chain alkyl or alkenyl group.

[0022] Furthermore, the R1 and R3 may all be the same, and may be an alkyl group or an alkenyl group.

[0023] Furthermore, the R1 to R3 may all be the same, and may be an alkyl group or an alkenyl group.

[0024] Furthermore, the viscosity of the lanthanum group metal thin film-forming precursor may be 100 cP or less, preferably 80 cP or less, and more preferably 60 cP or less.

[0025] Furthermore, the melting point of the lanthanum group metal thin film forming precursor may be 100° C. or lower, preferably 80° C. or lower, and more preferably 60° C. or lower.

[0026] In addition, the thin film forming precursor may further contain a solvent, and the solvent may be C1-C 16 The thin film forming precursor may contain 1 to 99 wt % of the solvent relative to the total weight of the thin film forming precursor.

[0027] The method for forming a lanthanum group metal film of the present invention is characterized in that it includes a process of forming a thin film on a substrate using the thin film forming precursor, and the process of forming a thin film on a substrate includes a process of forming a precursor film by depositing the thin film forming precursor on the surface of the substrate and a process of reacting the precursor film with a reactive gas.

[0028] Furthermore, the step of forming a precursor thin film may include a step of vaporizing the thin film forming precursor and transferring the vaporized thin film forming precursor into a chamber.

[0029] In addition, the deposition can be performed by one of the following projects: spin-on dielectric (SOD) project, low temperature plasma (LTP) project, chemical vapor deposition (CVD) project, plasma chemical vapor deposition (PECVD) project, high density plasma chemical vapor deposition (HDPCVD) project, atomic layer deposition (ALD) project or plasma atomic layer deposition (PEALD) project.

[0030] Furthermore, the process of forming a lanthanum group metal-containing thin film on a substrate may include a step of forming the thin film by supplying the thin film forming precursor to the substrate and applying plasma.

[0031] Furthermore, a semiconductor device of the present invention is characterized by including a thin film manufactured by the above-mentioned method for forming a lanthanum group metal-containing thin film.

[0032] According to the precursor for forming a lanthanum-containing metal film of the present invention, it contains cyclopentadienyl and amidine ligands, so the precursor compound has excellent structural stability and exhibits the characteristics of low viscosity, high volatility, heat resistance, and a liquid state at room temperature or a solid state with a low melting point, thereby exhibiting physical properties suitable for use in the lanthanum-containing metal film formation process.

[0033] Furthermore, a lanthanum group metal-containing thin film can be formed using the precursor, and a semiconductor device including the lanthanum group metal-containing thin film manufactured by the thin film formation method can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is the nuclear magnetic resonance hydrogen spectrum of the precursor compound obtained by the preparation method of Example 1 ( 1 H-NMR) analysis results.

[0035] Figure 2 This is the result of thermogravimetric analysis (TGA) of the precursor compound obtained by the production method of Example 1.

[0036] Figure 3 This is the differential scanning calorimetry (DSC) analysis result of the precursor compound obtained by the production method of Example 1.

[0037] Figure 4 This is the result of thermogravimetric analysis (TGA) of the precursor compound obtained by the production method of Example 2.

[0038] Figure 5 This is the result of thermogravimetric analysis (DSC) of the precursor compound obtained by the production method of Example 2.

[0039] Figure 6 This is the differential scanning calorimetry (TGA) analysis result of the precursor compound obtained by the production method of Example 3.

[0040] Figure 7 This is the differential scanning calorimetry (DSC) analysis result of the precursor compound obtained by the production method of Example 3.

[0041] Figure 8 This is the differential scanning calorimetry (TGA) analysis result of the precursor compound obtained by the production method of Example 4.

[0042] Fig. 9 This is the result of thermogravimetric analysis (DSC) of the precursor compound obtained by the production method of Example 4.

[0043] Fig.10 is the nuclear magnetic resonance hydrogen spectrum of the precursor compound obtained by the preparation method of Example 5 ( 1 H-NMR) analysis results.

[0044] Fig.11 This is the differential scanning calorimetry (TGA) analysis result of the precursor compound obtained by the production method of Example 5.

[0045] Fig.12 This is the result of thermogravimetric analysis (DSC) of the precursor compound obtained by the production method of Example 5.

[0046] Fig.13 This is a graph plotting saturation conditions in a thin film formed using the precursor compound of Example 3 according to different precursor supply times.

[0047] Fig.14 This is a graph illustrating the change in film thickness according to different deposition cycle numbers in a thin film formed using the precursor compound of Example 3.

[0048] Fig.15 This is a graph illustrating the change in film deposition rate according to different process temperatures in a thin film formed using the precursor compound of Example 3.

[0049] Fig.16The X-ray diffraction (XRD) analysis results are used to confirm the crystallinity of the thin film formed using the precursor compound of Example 3 according to different process temperatures, and are the analysis results of the Gd2O3 thin film formed on the Si substrate (a) and the Gd2O3 thin film formed on the TiN substrate (b).

[0050] Fig.17 It is the X-ray diffraction (XPS) analysis result of the Gd2O3 thin film formed on the TiN substrate.

[0051] Fig.18 This is a conceptual diagram illustrating a metal-insulator-metal (MIM) structure in which TiN is deposited as an upper electrode on a Gd2O3 thin film formed on a TiN substrate.

[0052] Fig.19 This is a graph showing the temperature change in a thin film formed using the precursor compound of Example 2 according to different process cycle numbers.

[0053] Fig. 20 It is the X-ray diffraction (XRD) analysis result of the CeO2 thin film formed on the substrate using the precursor compound of Example 2. DETAILED DESCRIPTION

[0054] Next, the present invention will be described in more detail. The terms or words used in this specification and claims should not be interpreted in a general or dictionary sense, but should be interpreted based on the principle that the inventor can appropriately define the concept of the term in order to describe his invention in the best way, so as to conform to the meaning and concept of the technical idea of ​​the present invention.

[0055] The precursor for forming a lanthanum group metal-containing thin film according to the present invention is characterized by including a compound represented by the following Chemical Formula 1.

[0056]

Chemical formula 1

[0057]

[0058] In the chemical formula, M is a lanthanide metal, R1 and R3 are each independently a C1-C5 straight chain, branched or cyclic alkyl or alkenyl group, R2 is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, R' is the same as or different from each other and is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, and n is an integer from 1 to 5.

[0059] The lanthanum metals are 15 elements ranging from lanthanum (La) with an atomic number of 57 to lutetium (Lu) with an atomic number of 71, which may include lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu).

[0060] In the chemical formula 1, R1 and R3 constituting the amidine ligand may be the same or different, and may be constituted in various forms according to the desired effect to be achieved by the precursor provided by the present invention.

[0061] In addition, in the chemical formula 1, R2 constituting the amidine ligand may be a hydrogen atom or a C1-C4 linear, branched or cyclic alkyl or alkenyl group, and as a non-limiting example, may include n-alkyl groups such as ethyl, propyl and butyl.

[0062] The compound represented by Chemical Formula 1 is a precursor of a chemical structure having a lanthanum metal as a central metal atom and containing an amidine ligand, comprising a cyclopentadienyl ligand that can achieve properties such as a low melting point and high volatility, and also comprising a new amidine ligand that is different from the current ones, thereby being able to impart properties such as higher structural stability, low viscosity, high volatility, high heat resistance, and a liquid form at room temperature or a solid state with a low melting point.

[0063] That is, the precursor for forming a lanthanum group metal film according to the present invention uses a lanthanum group metal as the central metal and contains different types of ligands that can make different contributions to improving the performance of the precursor, especially a new type of amidine ligand that can achieve outstanding effects such as structural stability, low viscosity, high volatility, high heat resistance, and a liquid state at room temperature or a solid state with a low melting point, thereby exhibiting physical properties suitable for use in thin film formation engineering and thereby forming high-quality thin films.

[0064] The thin film forming precursor represented by the chemical formula 1 may have various forms having different functional groups.

[0065] As one embodiment, the R2 can be a straight chain, branched or cyclic alkyl or alkenyl group of C2-C4. When R2 is C2 or above, the intramolecular symmetry can be increased compared to the case of C1, thereby reducing the mutual interference between molecules, so that the precursor containing the ligand can be easily formed in a liquid state or a solid state with a lower melting point, and low viscosity characteristics can also be achieved.

[0066] In addition, the R1 and R3 may each independently be a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.

[0067] Furthermore, in one embodiment, the R1 and R3 may be methyl groups, and the R2 may be isopropyl groups.

[0068] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group.

[0069] Compared with branched or cyclic alkyl or alkenyl groups, straight chain alkyl or alkenyl groups can reduce the molecular weight by minimizing the structure of the ligand and thereby achieve the effect of improving volatility and vapor pressure.

[0070] Therefore, in the ligand according to one embodiment of the present invention, R1 and R3 can each be composed of a straight-chain alkyl group or an alkenyl group. In the above case, the vapor pressure of the thin film forming precursor containing the ligand can be increased, thereby achieving effects such as improving engineering convenience in the thin film forming process using the precursor.

[0071] In addition to the vapor pressure improvement effect, in the ligand in which R1 and R3 are each composed of a straight-chain alkyl group, the structural freedom of the ligand is high, so the freedom of the precursor applicable to the ligand can be improved. With the above effect, the interference between the precursors can be minimized, thereby achieving the effect of achieving the liquefaction and low viscosity characteristics of the precursor.

[0072] Therefore, in the amidine ligand according to one embodiment of the present invention, R1 and R3 in the chemical formula 1 can be composed of a straight-chain alkyl group or an alkenyl group. In the above case, the vapor pressure of the precursor containing the ligand can be increased, and it can be easily formed in a liquid state or a solid state with a lower melting point by increasing the degree of freedom, and low viscosity characteristics can also be achieved at the same time.

[0073] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group, and the R2 may be a C1-C4 straight-chain alkyl or alkenyl group.

[0074] Furthermore, the R1 and R3 may all be the same, and may be C1-C5 linear, branched or cyclic alkyl or alkenyl groups.

[0075] Furthermore, the R1 to R3 may all be the same, and may be C1-C4 linear, branched or cyclic alkyl or alkenyl groups.

[0076] An exemplary structure of the thin film forming precursor represented by Chemical Formula 1 as described above is as follows. In the following structure, Ln refers to a lanthanum metal, which is 15 elements including lanthanum (La) with an atomic number of 57 to lutetium (Lu) with an atomic number of 71, and may include lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu).

[0077]

[0078]

[0079]

[0080] In addition, the cyclopentadienyl ligand has a substituted structure, thereby adjusting the size of the molecule and further adjusting the viscosity and volatility of the compound.

[0081] The viscosity of the lanthanum group metal thin film forming precursor may be 100 cP or less, preferably 80 cP or less, and more preferably 60 cP or less. In addition, the melting point of the thin film forming precursor may be 100° C. or less, preferably 80° C. or less, and more preferably 60° C. or less.

[0082] By adopting the chemical structure of the thin film forming precursor as described above, a liquid precursor having low viscosity, high heat resistance and high volatility can be obtained, thereby forming a high-quality thin film.

[0083] In addition, considering the conditions and efficiency of the thin film forming process, the thin film forming precursor of the present invention may further contain a solvent for dissolving or diluting the precursor compound. As the solvent, C1-C 16 One or a mixture of saturated or unsaturated hydrocarbons, ketones, ethers, glycol dimethyl ether, esters, tetrahydrofuran and tertiary amines. 16 Examples of saturated or unsaturated hydrocarbons include pentane, cyclohexane, ethylcyclohexane, heptane, octane and toluene, and examples of tertiary amines include dimethylethylamine and triethylamine.

[0084] In particular, the compound of the thin film forming precursor may be in a solid state at room temperature according to its chemical structure, and in the case as described above, the compound can be dissolved by including the solvent. That is, when the solvent is included, the solvent that can dissolve the precursor compound and the content thereof are preferably 1 to 99% by weight relative to the total weight of the thin film forming precursor.

[0085] Since the precursor containing or not containing the solvent can be gasified, it can be supplied into the chamber in the form of precursor gas. Therefore, depending on the type of the precursor compound for thin film formation, when it exists in a liquid state at room temperature and can be easily gasified, a thin film formation process can be performed without using a separate solvent.

[0086] In addition, the lanthanum-containing metal film formation process can be performed by one of the following processes: spin-ondielectric (SOD) process, low temperature plasma (LTP) process, chemical vapor deposition (CVD) process, plasma chemical vapor deposition (PECVD) process, high density plasma chemical vapor deposition (HDPCVD) process, atomic layer deposition (ALD) process or plasma atomic layer deposition (PEALD) process.

[0087] For example, when the high-density plasma chemical vapor deposition (HDP-CVD) process is applied, it can be performed under high vacuum and high power compared to the atmospheric pressure chemical vapor deposition process (AP-CVD), low pressure chemical vapor deposition process (LP-CVD) or plasma enhanced chemical vapor deposition process (PE-CVD), so a thin film with a dense structure and excellent mechanical properties can be formed.

[0088] To this end, the thin film forming method according to the present invention includes a step of forming a thin film on a substrate using the thin film forming precursor.

[0089] Specifically, the process of forming a lanthanum group metal-containing thin film on the substrate may include a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of the substrate and a process of reacting the precursor thin film with a reactive gas.

[0090] Furthermore, the method may include a step of vaporizing the thin film forming precursor and transferring the vaporized thin film forming precursor into a chamber for deposition of the precursor.

[0091] In addition, the process of forming a lanthanum group metal-containing thin film on the substrate may include a process of forming a thin film of metal, oxide, nitride, oxynitride, etc. by supplying the thin film forming precursor to the substrate and applying plasma in the presence of a reactive gas.

[0092] The film forming process can be performed under a chamber pressure condition of 1 to 10 Torr. In addition, the source power for forming plasma in the chamber is preferably 500 to 9,000 W, and the bias power is preferably 0 to 5,000 W. In addition, the bias power may not be applied according to specific circumstances.

[0093] In addition, the process of forming a thin film on the substrate is preferably performed at a temperature ranging from 150 to 500°C.

[0094] In addition, when supplying the thin film forming precursor, in order to further improve the electrical properties of the metal film finally formed, i.e., the electrostatic capacitance or the leakage current value, a second metal precursor can be introduced as needed. As the second metal precursor, a metal precursor containing one or more metals (M") selected from magnesium (Mg), strontium (Sr), barium (Ba), lanthanum elements (Ln), titanium (Ti), zirconium (Zr), hafnium (Hf), niobium (Nb), tantalum (Ta), aluminum (Al), indium (In), silicon (Si), germanium (Ge) and tin (Sn) atoms can be selectively further supplied. The second metal precursor can be an alkylamide compound or an alkoxy compound containing the metal. As an example, when the metal is Si, SiH(N(CH3)2)3, SiH2(N(C2H5)2)2, SiH2(NH t Bu)2、SiH3(N( i Pr)2), Si(OC4H9)4, Si(OC2H5)4, Si(OCH3)4 and Si(OC(CH3)3)4, etc.

[0095] The supply of the second metal precursor may be performed in the same manner as the supply method of the thin film forming precursor, the second metal precursor may be supplied together with the precursor onto the thin film forming substrate, or may be supplied sequentially after the supply of the precursor is completed.

[0096] In order to contact the thin film forming substrate, the thin film forming precursor and the optional second metal precursor as described above are preferably maintained at a temperature of 50 to 250° C., preferably 100 to 200° C. before being supplied into the reaction chamber.

[0097] In addition, after the precursor supply step and before the reactive gas is supplied, an engineering of purging an inert gas such as argon (Ar), nitrogen (N2) or helium (He) into the reactor can be performed to help the precursor and the optional second metal precursor move to the top of the substrate, or to form a pressure suitable for deposition in the reactor, and to discharge impurities and the like present in the chamber to the outside. At this time, it is preferable to make the pressure in the reactor reach 1 to 5 Torr by purging the inert gas.

[0098] In addition, as the reactive gas, one or a mixture of water vapor (H2O), oxygen (O2), ozone (O3), hydrogen peroxide (H2O2), hydrogen (H2), ammonia (NH3), nitric oxide (NO), nitrous oxide (N2O), nitrogen dioxide (NO2), hydrazine (N2H4) and silane (SiH4) can be used. When the process is carried out in the presence of an oxidizing gas such as water vapor, oxygen and ozone, a metal oxide film can be formed, and when the process is carried out in the presence of a reducing gas such as hydrogen, ammonia, hydrazine and silane, a metal monomer or a metal nitride film can be formed. In addition, a metal oxynitride film can be formed by mixing reactive gases.

[0099] In addition to the plasma treatment, a treatment process by heat treatment or light irradiation may be performed to provide thermal energy for depositing the thin film forming precursor, and the treatment process may be performed according to a general method. Preferably, in order to produce a thin film having a desired physical state and composition at a sufficient growth rate, the treatment process is performed at a substrate temperature of 100 to 1,000° C., preferably 250 to 600° C. in the reactor.

[0100] In addition, during the processing process, the process of purging an inert gas such as argon (Ar), nitrogen (N2) or helium (He) into the inside of the reactor as described above can also be performed to help the reactive gas move to the top of the substrate, or to form a pressure suitable for deposition in the reactor, and to discharge impurities or by-products present in the reactor to the outside.

[0101] The thin film can be formed by taking the above-mentioned steps of charging the thin film forming precursor, charging the reactive gas, and charging the inert gas as one cycle and repeating the cycle one or more times.

[0102] Furthermore, by applying the thin film forming process, various semiconductor devices including thin films can be manufactured.

[0103] Next, the effects of the precursor according to the present invention will be described through examples.

[0104] Example 1: Synthesis of bis(ethylcyclopentadienyl)(diethyl-acetamidine)lanthanum [(EtCp)2La(Et2Et-AMD)]

[0105] 20.0 g (0.0815 mol) of LaCl3 and Tetrahydrofuran (THF) is added to The mixture was placed in Schlenk flask A and stirred for 6 hours. Put the 15.36 g (0.1631 mol) of ethylcyclopentadiene was slowly added dropwise at 0°C to tetrahydrofuran (THF) and 3.91 g (0.163 mol) of NaH, and then stirred at room temperature for 12 hours to produce Na-EtCp. Na-EtCp produced by the above method was added dropwise to Schlenk flask A at 0°C and stirred at room temperature for 6 hours. Tetrahydrofuran (THF) and 10.46 g (0.0815 mol) of diethyl-acetamidine were placed in a Schlenk flask C and slowly added dropwise at 0°C. (1.00 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was added and stirred at room temperature for 1 hour. The synthesized Li-(Et2nPr-AMD) mixture solution was added dropwise to Schlenk flask A at 0°C and stirred at room temperature for 6 hours, and then the solvent was removed by decompression. The mixture obtained in the above manner was extracted and filtered with toluene, and the solvent and volatile substances were evaporated under vacuum conditions. The residual liquid after evaporation was distilled and purified at 185°C and 44mTorr to obtain a light yellow solid. The yield was 23.14g (63.0%). H NMR spectrum ( 1 HNMR) analysis results are as follows Figure 1 As shown, the peak characteristics described below are obtained.

[0106] 1 HNMR(C6D6,25℃):0.86(t,3H),1.04(t,6H),1.30(broad,6H),1.89(q,2H),2.62(broad,4H),3.00(q,4H),6.0(broad,8H).

[0107] The light yellow solid was stirred under nitrogen flow rate of During the analysis period, TGA (TA instrument company's SDTQ600) was used to measure the temperature at a temperature rise rate of 10°C / min in an environment. 1 / 2The value is 232.4°C, and the residual mass is 1.2% at 350°C, which means there is almost no residual mass. The results are shown as the results of thermogravimetric analysis (TGA) analysis showing the weight loss percentage according to the temperature change. Figure 2 shown.

[0108] In addition, the light yellow solid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 of TAinstrument) and maintained at 40°C for 10 minutes. During the DSC analysis, the temperature was increased at a rate of 10°C / min, and a decomposition peak was observed at 400°C. The results are the results of the DSC analysis showing the change in thermal energy according to the temperature change. Figure 3 shown.

[0109] Example 2: Synthesis of bis(isopropylcyclopentadienyl)(diethyl-n-propylamidino)cerium [(iPrCp)2Ce(Et2nPr-AMD)]

[0110] Towards 6.13 g (0.256 mol) of NaH and of tetrahydrofuran and slowly drop 11.54 g (0.081 mol) of diethyl-n-propionamidate and 17.56 g (0.162 mol) of isopropylcyclopentadiene at 0°C. Stir at room temperature for 12 hours to produce a mixture solution of Na-EtCp and Na-(Et2Et-AMD). Cool the Schlenk flask containing the reactants to -10°C and slowly add 20 g (0.081 mol) of cerium chloride. Stir at room temperature for 12 hours and evaporate under vacuum. The obtained liquid is distilled and purified at 250°C and 50 mTorr to obtain a dark purple liquid. The yield is 29.5 g (73.4%).

[0111] The dark purple liquid was stirred at a nitrogen flow rate of During the analysis period, TGA (TA instrument company's SDTQ600) was used to measure the temperature at a temperature rise rate of 10°C / min in an environment. 1 / 2 The value is 247.4°C, and the residual mass is 1.1% at 350°C, which means there is almost no residual mass. The results are shown as the results of thermogravimetric analysis (TGA) analysis showing the weight loss percentage according to the temperature change. Figure 4 As shown in FIG. 1 , the target compound was confirmed to have been synthesized by thermogravimetric analysis (TGA) analysis results showing a volatilization curve.

[0112] In addition, during the differential scanning calorimetry (DSC, TAinstrument Discovery 25) analysis, in which a dark purple liquid sample was placed in a sealed container for differential scanning calorimetry (DSC) and maintained at 40°C for 10 minutes and then measured at a heating rate of 10°C / min, a decomposition peak was observed at 399°C. The above results are the results of differential scanning calorimetry (DSC) analysis that show the change in thermal energy due to temperature change. Figure 5 shown.

[0113] Example 3: Synthesis of bis(ethylcyclopentadienyl)(diethyl-acetamidine)gadolinium [(EtCp)2Gd(Et2Et-AMD)]

[0114] Towards 6.13 g (0.256 mol) of NaH and of tetrahydrofuran and slowly drop 11.54 g (0.081 mol) of diethyl-n-propionamidate and 17.56 g (0.162 mol) of isopropylcyclopentadiene at 0°C. Stir at room temperature for 12 hours to produce a mixture solution of Na-EtCp and Na-(Et2Et-AMD). Cool the Schlenk flask containing the reactants to -10°C and slowly add 20 g (0.081 mol) of gadolinium chloride. Stir at room temperature for 12 hours and evaporate under vacuum. The obtained liquid is distilled and purified at 250°C and 50 mTorr to obtain a light yellow liquid. The yield is 29.5 g (73.4%).

[0115] The light yellow liquid was stirred at a nitrogen flow rate of During the analysis period, TGA (TA instrument company's SDTQ600) was used to measure the temperature at a temperature rise rate of 10°C / min in an environment. 1 / 2 The value is 224°C and the residual mass is 2% at 350°C. The results are shown as the results of thermogravimetric analysis (TGA) analysis showing the weight loss percentage according to temperature change. Figure 6 As shown in FIG. 1 , the target compound was confirmed to have been synthesized by thermogravimetric analysis (TGA) analysis results showing a volatilization curve.

[0116] In addition, a pale yellow liquid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 of TAinstrument) and maintained at 40°C for 10 minutes. During the DSC analysis period, the temperature was increased at a rate of 10°C / min, and a decomposition peak was observed at 412°C. The above results are the results of differential scanning calorimetry (DSC) analysis showing the change in thermal energy according to the temperature change. Figure 7 shown.

[0117] In order to measure the viscosity of the pale yellow liquid, analysis was performed using a viscometer (DV2T viscometer manufactured by Brookfield Ametek) in a nitrogen atmosphere, and it was confirmed that the liquid had a relatively low viscosity of 31 cP at 25°C.

[0118] Example 4: Synthesis of bis(ethylcyclopentadienyl)(diethyl-acetamidine)dysprosium [(EtCp)2Dy(Et2Et-AMD)]

[0119] Towards into the Schlenk flask of tetrahydrofuran (THF), 9.54 g (0.0744 mol) of diethyl-acetamidine ester and 14.29 g (0.1489 mol) of ethylcyclopentadiene and cooled to 0°C. To the cooled solution was added (0.2233 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was added and stirred at room temperature for 1 hour to produce a mixture solution of Li-EtCp and Li-(Et2Et-AMD). The Schlenk flask containing the reactants was cooled to 0°C and 20 g (0.0744 mol) of dysprosium chloride was added. After stirring at room temperature for three hours, the light green liquid obtained by evaporation under vacuum was distilled and purified at 170°C and 58 mTorr to obtain a light green liquid. The yield was 19.7 g (55.6%).

[0120] The light green liquid was stirred at a nitrogen flow rate of During the analysis period, TGA (TA instrument company's SDTQ600) was used to measure the temperature at a temperature rise rate of 10°C / min in an environment. 1 / 2 The value is 225.8°C, and the residual mass is 1.58% at 350°C, which means there is almost no residual mass. The results are shown as the results of thermogravimetric analysis (TGA) analysis showing the weight loss percentage according to the temperature change. Figure 8 As shown in FIG. 1 , the target compound was confirmed to have been synthesized by thermogravimetric analysis (TGA) analysis results showing a volatilization curve.

[0121] In addition, the light green liquid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 of TA Instrument Co., Ltd.) and maintained at 40°C for 10 minutes. During the DSC analysis period, the temperature was increased at a rate of 10°C / min, and a decomposition peak was observed at 418°C. The results are the results of the DSC analysis showing the change in thermal energy according to the temperature change. Fig. 9 shown.

[0122] Furthermore, in order to measure the viscosity of the light green liquid, analysis was performed using a viscometer (DV2T viscometer manufactured by Brookfield Ametek) in a nitrogen atmosphere, and it was confirmed that the liquid exhibited a low viscosity of 38 cP at 25°C.

[0123] Example 5: Synthesis of bis(ethylcyclopentadienyl)(diethyl-acetamidine)lutetium [(EtCp)2Lu(Et2Et-AMD)]

[0124] Towards into the Schlenk flask of tetrahydrofuran (THF), 9.12 g (0.0711 mol) of diethyl-acetamidine ester and 13.39 g (0.1422 mol) of ethylcyclopentadiene and cooled to 0°C. To the cooled solution was added (0.2133 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was added and stirred at room temperature for 1 hour to produce a mixture solution of Li-EtCp and Li-(Et2Et-AMD). The Schlenk flask containing the reactants was cooled to 0°C and 20 g (0.0711 mol) of lutetium chloride was added. After stirring at room temperature for three hours, the brown liquid was evaporated under vacuum and distilled and purified at 170°C and 55 mTorr to obtain an orange-yellow liquid. The yield was 22.4 g (64.5%). Nuclear magnetic resonance hydrogen spectrum ( 1 H NMR) analysis results are as follows Fig.10 As shown, the peak characteristics described below are obtained.

[0125] 1 H NMR(C6D6,250C):0.83(t,3H),0.98(t,6H),1.19(q,6H),1.93(q,2H),2.44(q,4H),3.00(q,4H),6.0(broad,8H).

[0126] In addition, the orange-yellow liquid was During the analysis period, TGA (TA instrument company's SDT Q600) was used to measure the temperature at a temperature rise rate of 10°C / min in an environment. 1 / 2 The value is 223°C, and the residual mass is 1.4% at 350°C, which means there is almost no residual mass. The results are shown as the results of thermogravimetric analysis (TGA) analysis showing the weight loss percentage according to temperature change. Fig.11 shown.

[0127] In addition, during the analysis of differential scanning calorimetry (DSC, TAinstrument Discovery 25), in which the orange-yellow liquid sample was placed in a sealed container for differential scanning calorimetry (DSC) and maintained at 40°C for 10 minutes and then measured at a heating rate of 10°C / min, a decomposition peak was observed at 455°C. The above results are the results of differential scanning calorimetry (DSC) analysis that show the change in thermal energy due to temperature change. Fig.12 shown.

[0128] In order to measure the viscosity of the orange-yellow liquid, analysis was performed using a viscometer (DV2T viscometer manufactured by Brookfield Ametek) in a nitrogen atmosphere, and it was confirmed that the orange-yellow liquid exhibited a relatively low viscosity of 38 cP at 25°C.

[0129] Production Example 1: Thin film formation process using the precursor compound of Example 3

[0130] The atomic layer deposition process was performed in a bubbler manner using the precursor compound of Example 3 and O3 as an oxidant, and a film formation evaluation was performed. The film thickness change (Number of cycles vs. Thickness) according to the number of process cycles was used as an indicator for the film formation evaluation. After the precursor compound of Example 3 was heated to the vaporization temperature, argon (Ar) gas was injected through the production line (Dip line) to generate bubbles, so that the vapor of the precursor compound of the gas yellow stage was supplied to the interior of the reaction chamber with the help of a transport gas.

[0131] SiO2 substrates and TiN substrates were placed in the reaction chamber and deposition evaluation was performed while changing the precursor supply time, purge time, oxidant supply time, and purge time conditions to confirm the change in film thickness according to the number of process cycles while maintaining the set temperature (300°C). The purge process was performed using argon (Ar) gas at a flow rate of 700 sccm, and ozone (O3) as a reaction gas was used at a flow rate of 220 g / m 3The precursor was heated to 100°C and the injection amount of argon carrier gas was 200 sccm. The saturation condition according to the precursor supply time was confirmed under the deposition condition of 300°C. The results are as follows: Fig.13 shown.

[0132] pass Fig.13 The results show that saturation occurs when the precursor supply time is 14 seconds under the corresponding engineering conditions.

[0133] In addition, in order to confirm the change of film thickness according to the number of process cycles, the number of cycles was 50, 100, 150 and 200. The results of the change of film thickness according to the number of cycles are as follows: Fig.14 shown.

[0134] Through Fig.14 The film thickness change of the SiO2 test piece evaluated by the results was confirmed according to the number of deposition cycles, and the film deposition rate (GPC, Growth per cycle) was confirmed to be approximately 0.079nm / cycle.

[0135] In addition, in order to confirm the change in the low-value film deposition rate according to the process temperature (ALD window), after the precursor according to Example 3 is heated to the vaporization temperature, argon (Ar) gas is injected through the production line (DIP line) to generate bubbles, so that the vapor of the precursor compound of the gaseous phase is supplied to the interior of the reaction chamber with the help of a carrier gas.

[0136] SiO2 and TiN substrates were placed in the reaction chamber and supplied in the order of precursor (14 seconds) - purge (140 seconds) - oxidant (10 seconds) - purge (30 seconds) in order to confirm the change in film deposition rate according to process temperature (250, 280, 300, 320, 350°C) while changing the temperature. As purge gas, argon (Ar) gas was supplied at a flow rate of 70 sccm. As reaction gas, argon (Ar) gas was supplied at a flow rate of 220 g / m 3 The precursor was heated to 100°C, and the injection rate of argon carrier gas was 200 sccm. The number of processes was 50. The film deposition rate changes according to the process temperature are shown in the following figure. Fig.15 shown.

[0137] like Fig.15The results show that at process temperatures (250°C, 280°C, and 300°C), a similar film deposition rate of about 0.09nm / cycle is shown, which confirms that the process temperature range (ALD window) has the same film thickness. In addition, it can be confirmed that at 320 and 350°C, the film deposition rate (GPC) tends to decrease slightly.

[0138] In addition, in order to confirm the crystallinity of the thin film at different process temperatures, X-ray diffraction (XRD) analysis was performed on the Gd2O3 thin films obtained at different temperatures in the SiO2 and TiN test pieces through the process evaluation, thereby confirming the crystallinity of the thin film. The crystallinity was measured after the deposition process at 300°C and 320°C, and the test pieces were also analyzed after heat treatment using rapid thermal annealing (RTA) at 600°C, 60 seconds and N2 conditions. The analysis results show that regardless of the type of substrate, the crystallinity of Gd2O3 composed of a mixture of monoclinic and cubic crystal systems was observed in the measured diffraction pattern, and it can be confirmed that compared with 300°C, the crystallization to the cubic phase was promoted at 320°C. The crystallinity did not show a large change according to the heat treatment, and it can be confirmed that the crystallinity of the sample deposited at 320°C was slightly improved after heat treatment. The analyzed X-ray diffraction (XRD) results are as follows Fig.16 shown.

[0139] In addition, X-ray electron spectroscopy depth analysis (XPS depth profile) was performed to confirm the composition and impurities of the film. For the Gd2O3 film deposited at 300°C on a TiN substrate, the composition and impurity content of the film were confirmed by X-ray electron spectroscopy (XPS) analysis. It was observed that the C and N impurities in the film were both 0%, and the O / Gd content ratio was observed to be about 2.5, with an oxygen-rich composition ratio. The results of the analyzed X-ray electron spectroscopy depth analysis (XPS depth profile) are as follows: Fig.17 shown.

[0140] In addition, in order to evaluate the electrical properties of the films, Fig.18 In the manner shown, a metal-insulator-metal (MIM) structure was produced in which a Gd2O3 film with a thickness of 10 nm was deposited on a TiN substrate at 300°C and 320°C, and TiN was deposited as an upper electrode.

[0141] The results of confirming the dielectric constant and leakage current characteristics of the Gd2O3 thin film in the manufactured components are shown in Table 1.

[0142]

Table 1

[0143]

[0144] From these results, it was confirmed that the produced thin film can be used as a thin film for improving the characteristics of a dielectric film.

[0145] Production Example 2: Thin film formation process using the precursor compound of Example 2

[0146] Film formation evaluation by an atomic layer deposition process was performed using the precursor of Example 2 and O 3 as an oxidant in a bubbler manner.

[0147] SiO2 substrates and TiN substrates were placed in the reaction chamber and the deposition evaluation was carried out under the conditions of precursor (40 seconds)-purge (80 seconds)-oxidant (15 seconds)-purge (30 seconds) to confirm the change in film thickness according to the number of process cycles while maintaining the set temperature (280°C). The purge process was performed using argon (Ar) gas at a flow rate of 700 sccm, and ozone (O3) as a reaction gas was used at a flow rate of 200 g / m 3 The precursor was heated to 110° C., the amount of argon carrier gas injected was 200 sccm, and the temperature of the gas moving pipe was set to 120° C., and a Ce-containing thin film was formed by 100 processes.

[0148] It was confirmed that the film deposition rate (GPC) of the formed film was 0.088 nm / cycle and the density (density) of the formed film was 4.74 g / cm 3 , and the roughness is 0.7nm, which is a good result. The analysis results are as follows Fig.19 shown.

[0149] In addition, the crystallinity of the film was analyzed to confirm its characteristics as a high dielectric constant film. It was confirmed that the film exhibited a cubic phase regardless of the substrate conditions, and that the film exhibited a cubic phase even at a relatively thin thickness of 4 nm. Fig. 20 shown.

[0150] From these results, it was confirmed that the produced thin film can be used as a thin film for improving the characteristics of a dielectric film.

[0151] The present invention has been described with reference to preferred embodiments in the above content, but the present invention is not limited to the embodiments, and a person having general knowledge in the technical field to which the present invention belongs can make various modifications and changes to the present invention without departing from the gist of the present invention. These modifications and changes should be understood to be included in the scope of the claims attached to the present invention.

Claims

1. A precursor for forming a lanthanum metal thin film, characterized in that: The invention comprises a lanthanum metal compound represented by the following chemical formula 1: 【Chemical formula 1】 In the chemical formula 1, M is a lanthanide metal, R1 and R3 are each independently a C1-C5 straight chain, branched or cyclic alkyl or alkenyl group, R2 is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, R' are the same as or different from each other and are a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, and n is an integer from 1 to 5.

2. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, R2 is a C2-C4 linear, branched or cyclic alkyl or alkenyl group.

3. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, R1 and R3 are each independently a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and R2 is a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.

4. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, R1 and R3 are methyl groups.

5. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, the R2 is an isopropyl group.

6. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, R1 and R3 are each independently a C1-C5 straight-chain alkyl or alkenyl group.

7. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, R1 and R3 are each independently a C1-C5 straight-chain alkyl or alkenyl group, and R2 is a C1-C4 straight-chain alkyl or alkenyl group.

8. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, R1 and R3 are all the same and are C1-C5 linear, branched or cyclic alkyl or alkenyl groups.

9. The method for forming a lanthanum-containing metal film according to claim 1, wherein: In the chemical formula 1, all of R1 to R3 are the same and are C1-C4 linear, branched or cyclic alkyl or alkenyl groups.

10. The method for forming a lanthanum-containing metal film according to claim 1, wherein: The viscosity of the lanthanum group metal thin film forming precursor is 100 cP or less.

11. The method for forming a lanthanum-containing metal film according to claim 1, wherein: The melting point of the lanthanum group metal thin film forming precursor is 100° C. or less.

12. The method for forming a lanthanum-containing metal thin film according to claim 1, wherein: The thin film forming precursor further contains a solvent.

13. The method for forming a lanthanum-containing metal film according to claim 12, wherein: The solvent is C1-C 16 One or more of saturated or unsaturated hydrocarbons, ketones, ethers, glycol dimethyl ether, esters, tetrahydrofuran and tertiary amines.

14. The method for forming a lanthanum-containing metal film according to claim 12, wherein: The solvent is contained in an amount of 1 to 99% by weight relative to the total weight of the thin film forming precursor.

15. The method for forming a lanthanum-containing metal thin film according to claim 1, wherein: The thin film forming precursor is at least one selected from the group consisting of the following structures:

16. A method for forming a lanthanum-containing metal film, characterized in that: The method comprises the step of forming a thin film on a substrate using the thin film forming precursor according to claim 1 or claim 12.

17. The method for forming a lanthanum-containing metal film according to claim 16, wherein: The process of forming a thin film on a substrate comprises: a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of a substrate; and The process of reacting the precursor film with a reactive gas.

18. The method for forming a lanthanum-containing metal film according to claim 17, wherein: The step of forming a precursor thin film includes a step of vaporizing the thin film forming precursor and transferring the vaporized precursor into a chamber.

19. The method for forming a lanthanum-containing metal film according to claim 17, wherein: The deposition is performed by one of a dielectric spin coating (spin-on dielectric, SOD) project, a low temperature plasma (Low Temperatur e Plasma, LTP) project, a chemical vapor deposition (Chemical Vapor Deposition, CVD), a plasma chemical vapor deposition (Plasma Enhanced Chemical Vapor Deposition, PECVD), a high density plasma chemical vapor deposition (High Density Plasma-Chemical Vapor Deposition, HDPCVD) project, an atomic layer deposition (Atomi c Layer Deposition, ALD) project or a plasma atomic layer deposition (Plasma-Enhanced Atomi c Layer Deposition, PEALD) project.

20. The method for forming a lanthanum-containing metal film according to claim 16, wherein: The process of forming a thin film on a substrate comprises: A step of forming a thin film by supplying the thin film forming precursor to a substrate and applying plasma.

21. A semiconductor component, characterized in that: It comprises a lanthanum group metal-containing thin film produced by the thin film forming method according to claim 16.

Citation Information

Patent Citations

  • Preparation of lanthanide-containing precursors and deposition of lanthanide-containing films

    KR101660052B1

  • Lanthanum precursors for depositing lanthanum, lanthanum oxide, and lanthanum nitride films.

    KR1020190008427A

  • Lanthanide precursors and deposition of lanthanide-containing films using the same

    KR1020190094238A

  • Lanthanum compound and methods of forming thin film and integrated circuit device

    KR1020190109142A

  • Yttrium / lanthanide-containing precursor compounds, precursor compositions including the same for forming films, and method of forming yttrium / lanthanide-containing films using the precursor composition

    KR1020210084297A